Model-Model Masyarakat dan Efektifitas Pelaksanaan Pendidikan Agama Islam - Mas'ud, Moh. Ali (LP2M Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: This paper reveals the models of society and the effectiveness of the implementation of Islamic religious education and has had a remarkable impact. Community models namely prismatic models, centralized models and dispersed models are written in this paper. The model is the paradigm by Riggs, the model is the context of the fundamental view of what is the subject matter in science. Prismatic models are community mix between traditional values and the modernization process in which there is an overlap (overlapping)between these two values. The centralized model is that all structures in a social system are so scattered that the so-called medeldiffractedand the dispersed model is that all structures in a social system are very specifically called focused which are taken from optical physics about light. The purpose of this paper is to know the models of society, namely the prismatic model, the centralized model and the dispersing model as the main problem of the social structure of the community and the effectiveness of implementing Islamic religious education, especially both public schools and schools under the auspices of the religious department. so that the quality of students gets better.